PROTOTIPE AUTOMATIC FEEDER DENGAN MONITORING IoT UNTUK PERIKANAN BIOFLOK LELE MASYARAKAT DUKUH PRAYUNAN - Maghfiroh, Hari; Hermanu, Chico; Adriyanto, Feri (Jurnal Abdimas, 2020)
The Industrial Revolution 4.0 has brought many changes both positive and negative. The positive aspect is that there has been much use of automation and robots in the industrial world so that production can increase rapidly. While the negative angle, more and more human work is replaced by machines so that it reduces job opportunities. The existence of the industrial revolution 4.0 also brought a gap between the technology literacy group and the technology stutterer group (gaptek). Villagers are a large group from the second class. For this reason, a new business opportunity that can be carried out by the village community with secondary education level is urgently needed. Then the catfish bio-floc fisheries program was chosen. A touch of automation technology and the Internet of Things (IoT) is given to increase productivity and make people literate about the technological development of the industrial revolution era 4.0.